The molecular mechanisms and intervention strategies of mitophagy in cardiorenal syndrome - Yao, Mengying; Liu, Yong; Sun, Mengjia; Qin, Shaozong; Xin, Wang; Guan, Xu; Zhang, Bo; He, Ting; Huang, Yinghui (Frontiers in Physiology, 2022)
Cardiorenal syndrome (CRS) is defined as a disorder of the heart and kidney, in which acute or chronic injury of one organ may lead to acute or chronic dysfunction of the other. It is characterized by high morbidity and mortality, resulting in high economic costs and social burdens. However, there is currently no effective drug-based treatment. Emerging evidence implicates the involvement of mitophagy in the progression of CRS, including cardiovascular disease (CVD) and chronic kidney disease (CKD). In this review, we summarized the crucial roles and molecular mechanisms of mitophagy in the pathophysiology of CRS. It has been reported that mitophagy impairment contributes to a vicious loop between CKD and CVD, which ultimately accelerates the progression of CRS. Further, recent studies revealed that targeting mitophagy may serve as a promising therapeutic approach for CRS, including clinical drugs, stem cells and small molecule agents. Therefore, studies focusing on mitophagy may benefit for expanding innovative basic research, clinical trials, and therapeutic strategies for CRS.